PENGARUH KENYAMANAN DAN KOMPATIBILITAS YANG DIRASAKAN PADA ADOPSI BELANJA ONLINE DIANTARA GENERASI X: PENDEKATAN TAM - Rafnelly Rafki; Suharno Prawirosumarto; Lusiana Lusiana; Silvia Sari; Yolanda Oktarina; Nofriadi Nofriadi (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
In recent years, online shopping has become more immersive and integrated in everyday life, especially due to lifestyle changes triggered by the COVID-19 pandemic. However, there are still individual doubts and differences in the adoption rate of online shopping among Generation X. Generation X, these are individuals born between 1965 and 1980, have become one of the major consumer groups in the online shopping ecosystem. Although Generation X has experience with technology and the internet, a number of factors still influence the adoption rate of online shopping among them. There has been a lot of research done on online shopping but studying the perceived Effect of Convenience and Compatibility on Online Shopping Adoption among Generation X and using the TAM Approach, there has not been much and is still needed. So the purpose of this study is to study the Effect of Convenience and Perceived Compatibility on Online Shopping Adoption among Generation X: TAM Approach. The study involved an online survey conducted on a sample consisting of members of Generation X who actively use online shopping services. Data was collected through questionnaires that included questions related to convenience factors, compatibility, as well as the adoption rate of online shopping. Multiple linear regression analysis is used to test the research hypothesis. The results of this study show that the perception of convenience has a significant positive influence on the adoption rate of online shopping among Generation X. In addition, compatibility factors have also been shown to have a positive effect on the adoption of online shopping. His contribution is that companies can develop more effective strategies to increase the adoption of online shopping among this generation.